(untitled) (PETITUM, 2014)
According to the laws of 39 and 2004 years about the Placement and Protection of Indonesian Labor in abroad that the protection of Indonesian labor is all efforts to protect the interests of Prospective or Indonesian Labor in ensuring the fulfillment of realizing their rights in accordance with laws and regulations, either before, during, and after they work This study used normative legal method and sociological legal or empirical research. This study aimed to obtain legal materials in answering the problems based on the fact, whether the rights of Indonesian Labor in the Timur Tengah who comes from Polewali Mandar protected or not. And what obstacles are faced in the rights protection of Indonesian labor? The conclusion of this study state the rights of Indonesian labor are not adequately protected. It is proved that there are still many rights and obligations of Prospective or Indonesian Labor who are not included in the contract of agreement so that it is not clear how the Prospective or Indonesian Labor in the field of civil is protected and can be enforced. Furthermore, there are number of constraints and problems that faced by Prospective or Indonesian Labor either in pre placement, placement, and after placement. Therefore, this study recommend to need maximizing the role of the parties in the employment field to escort and protect the interests of Prospective or Indonesian Labor. It’s main to encourage Prospective or Indonesian Labor to take part in designing, making and signing the contract of agreement, as part of the rights protection of prospective or Indonesian labor in the field of civil.